2010
DOI: 10.4269/ajtmh.2010.09-0447
|View full text |Cite
|
Sign up to set email alerts
|

The Incremental Cost-Effectiveness of Engaging Private Practitioners to Refer Tuberculosis Suspects to DOTS Services in Jogjakarta, Indonesia

Abstract: We aimed to evaluate the incremental cost-effectiveness of engaging private practitioners (PPs) to refer tuberculosis (TB) suspects to public health centers in Jogjakarta, Indonesia. Effectiveness was assessed for TB suspects notified between May 2004 and April 2005. Private practitioners referred 1,064 TB suspects, of which 57.5% failed to reach a health center. The smear-positive rate among patients reaching a health center was 61.8%. Two hundred eighty (280) out of a total of 1,306 (21.4%) new smear-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Although Ahmad et al (2009) concluded that actively finding cases would provide the best outcomes, that strategy may be less cost-effective than other strategies, including involvement of the private sector in the DOTS strategy. Mahendradhata et al (2010) conducted a study to evaluate the incremental cost-effectiveness of such an initiative in Yogyakarta province where private practitioners were engaged to refer patient suspected of TB to a healthcare centre for DOTS treatment. They concluded that this strategy could be cost-effective given a wellfunctioning DOTS programme.…”
Section: Discussionmentioning
confidence: 99%
“…Although Ahmad et al (2009) concluded that actively finding cases would provide the best outcomes, that strategy may be less cost-effective than other strategies, including involvement of the private sector in the DOTS strategy. Mahendradhata et al (2010) conducted a study to evaluate the incremental cost-effectiveness of such an initiative in Yogyakarta province where private practitioners were engaged to refer patient suspected of TB to a healthcare centre for DOTS treatment. They concluded that this strategy could be cost-effective given a wellfunctioning DOTS programme.…”
Section: Discussionmentioning
confidence: 99%
“…According to a WHO report, global grants for TB control have been increasing Financial support and material supply and technical resources 17 IND-1, 2 103,104 This may be the result of successful TB control activities and a stable reduction of TB prevalence, but most evaluations have argued that current funding is insufficient to sustain the scale-up of PPM in the long term and that more investment is urgently needed. 34,48,66,74 Therefore, the analysis of cost-effectiveness and expenditure reduction is an increasing requirement. Incentives, although not an essential condition, are always thought to be a useful approach to improve PPM participation and the service performance of physicians.…”
Section: Interpretation and Summarymentioning
confidence: 99%
“…For example, while many of the articles and abstracts described the potential returns of engaging retail drug outlets, none of the 12 full-text articles described the necessary inputs in terms of cost. TB programs that may need to prioritize among various PPM interventions must have an understanding of the estimated costs and cost effectiveness of each intervention [24, 25],. Such estimates, if modeled from pilot or small-scale initiatives, would allow TB programs to use a set amount of funding to determine which intervention would return the greatest output in terms of presumptive TB cases referred and ultimately confirmed.…”
Section: Discussionmentioning
confidence: 99%